PENGARUH LIKUIDITAS DAN SOLVABILITAS TERHADAP RETURN ON EQUITY (ROE) PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2004 – 2013 - admin, DEVI RAMADHANI B 111 10023 (Jurnal Manajemen Update, 2016)
The purpose of this Research is: to test and analyze the effect of liquidity and solvency toward return on equity (roe) on 5 mining companies : Pt bumi resource tbk, Pt aneka tambang tbk, Pt international nickle Indonesia tbk, Pt timah tbk, and PT medco energi international tb, from 2004 untill 2013. There is an analysis that been used is regression double linear analysis. The double regression analysis is an analysis which is use to the data with the shape of numbers and the way of study regression double linear with a statistic test. The result of analysis show that liquidity's variable (CR) has a significan to current ratio (CR) is 0,355 with a=0,05 so the significan > a. It means that current ratio (CR) is not effect to return on equity (roe), so the H1 : the current ratio (CR) is not effect to return on equity (roe) is rejected. The coefficient regression for solvency variable (x2) where the significan's score debt to equity (DER)  is 0,002 with a=0,05 so the significan < a. It means the influence of debt to equity (DER) is positively influential in measure alteration of return on equity (roe), so H2 : debt to equity is influential on return on equity (roe)  is accepted.   Keyword : liquidity and solvency toward return on equity (roe) on mining company.